PTH-070 Nurse Led One Stop Upper Gi Clinics Are Safe And Allow Rapid Assessment Of Patients With Suspected Gastro-oesophageal Malignancy. (9th June 2014) - Williams, S; Ashall, B; Cave, G; Bassi, A; Flanagan, PK
Abstract : Introduction: Meeting 2 week referral targets presents a challenge to many hospitals. Commonly patients are seen in clinic prior to investigation with resultant additional delays in time to investigation. Nurse led one stop clinics where patients undergo clinical assessment and endoscopic and/or radiological assessment on the same day have the potential to shorten time to investigation, allow rapid complete clinical assessment and meet the demand for 2 week wait (2WW) referrals. Methods: Aims: To assess the efficacy and safety of a nurse led one stop suspected upper GI cancer clinic in meeting 2 week targets. To determine outcomes for patients referred on a 2WW pathway. Methods: All patients referred to Whiston Hospital on a two week upper GI pathway within the 6 month period from November 2012 to April 2013 were assessed. Additionally all upper GI cancers diagnosed in the same period were separately analysed. Patients were identified using hospital IT systems and data collated on demographics, referring symptoms, investigations and patient outcomes. Analysis was performed using StatsDirect v2.6.8. Results: Complete data was available for 202 patients (61%). 40% of patients did not meet criteria for 2 week referral. One stop clinics enabled complete assessment and investigation of patients within 2 weeks (mean 11.6 ± 0.63 days). Time to first investigation was significantly quicker than patients seen in clinic (11.6 vs 18 days, p < 0.005, ANOVA) and was no different than open access endoscopy (11 days, p = 0.96). Cancers were identified in 15 (7.4%), of which only 8 (57%) were upper GI. No significant differences in patient outcome (time to investigation/pathology identified) were seen between nurse led and physician led clinics. In the same time period 53 upper GI cancers were diagnosed meaning only 15% were referred on a two week pathway. The presence of dysphagia was the commonest presenting symptom in upper GI malignancy (87%) but had a poor positive predictive value (15%). Conclusion: Nurse led one stop upper GI cancer clinics are safe, allow complete assessment and investigation of patients within 2 week wait (2WW) targets and improve time to test compared to standard clinics. Appropriateness of 2WW referrals remains low and many cancers are diagnosed outside this pathway. Further use of dedicated nurse led clinics may improve the ability for hospitals to meet service demands. Disclosure of Interest: S. Williams: None Declared, B. Ashall: None Declared, G. Cave: None Declared, A. Bassi: None Declared, P. Flanagan Grant/research support from: Awarded a Shire innovation fund for SpRs.